Signal management and risk minimization strategy: a case study on obinutuzumab and non-overt disseminated intravascular coagulation - Valdiserra, Giulia; Mores, Nadia; Rocchi, Rosalba Elisabetta; Sottosanti, Laura; Felicetti, Patrizia; Marchione, Pasquale; Laurenti, Luca; Fresa, Alberto; Bucaneve, Giampaolo; Cappello, Emiliano; Bonaso, Marco; Ferraro, Sara; et al. (Frontiers in Drug Safety and Regulation, 2023)
were reported 3 more ICSRs. The medical literature was poor of evidence about the possible association between obinutuzumab and DIC. The signal was subsequently validated, first by AIFA and then by EMA. The signal was confirmed by the Pharmacovigilance Risk Assessment Committee Rapporteur in the "signal confirmation" phase and it entered in the "signal analysis and prioritization" and the "signal assessment". In these phases, the PRAC assessed and confirmed DIC as a possible adverse reaction to obinutuzumab. Finally, the Summary of Product characteristics was updated with this new risk.Despite the intrinsic difficulties linked to the nature of the event itself, the process of the signal detection and the issuing of the risk minimization measures by the Italian Medicines Agency, as part of the EU procedures, has proven to be efficient.